Morphological Process of Affixation in Forming Code-Mixing Patterns on Instagram Quotes in 2023 to 2024 - Ela Lolitasari (PRASASTI: Journal of Linguistics, 2025)
The phenomenon of code-mixing involving Indonesian and English cannot be separated from the morphological process of affixation to form word formation patterns. This research is written with the formulation of the problem: 1) How is the process of affixation in forming code-mixing patterns in Quotes? 2) Why do speakers use the process of affixation in forming code-mixing patterns in Quotes? The research method used were qualitative method by focusing on data in the form of English words containing Indonesian affixes. Then the data was analyzed with a morphological approach based on affixation process. The result of this research showed that there was prefix di- to form passive sentences, prefix meN- to form active verbs, prefix ber- to form adjectives, and prefix se- to show intensity. The suffixes -nya, -ku, and -mu to show possession, and the suffix -an to form nouns. There was several factors that cause speakers to use the affixation process in forming code-mixing patterns, which are Intra-Lexical code-mixing, lack of grammar understanding, and technological developments.